NUClear: A Loosely Coupled Software Architecture for Humanoid Robot Systems - Houliston, Trent; Fountain, Jake; Lin, Yuqing; Mendes, Alexandre; Metcalfe, Mitchell; Walker, Josiah; Chalup, Stephan K. (Frontiers in Robotics and AI, 2016)
This paper discusses the design and interface of NUClear, a new hybrid message-passing architecture for embodied humanoid robotics. NUClear is modular, low latency and promotes functional and expandable software design. It greatly reduces the latency for messages passed between modules as the messages routes are established at compile time. It also reduces the number of functions that must be written using a system called co-messages which aids in dealing with multiple simultaneous data. NUClear has primarily been evaluated on a humanoid robotic soccer platform and on a robotic boat platform, with evaluations showing that NUClear requires fewer callbacks and cache variables over existing message-passing architectures. NUClear does have limitations when applying these techniques on multi-processed systems. It performs best in lower power systems where computational resources are limited. Future work will focus on applying the architecture to new platforms, including a larger form humanoid platform and a virtual reality platform and further evaluating the impact of the novel techniques introduced.